Eksistensi Hijab sebagai Upaya Perlindungan terhadap Wanita Muslimah Perspektif Maqāṣid al-Syarī’ah - Rosmita Rosmita; Qadriani Arifuddin; Sitti Aminah; Nasaruddin Nasaruddin (BUSTANUL FUQAHA: Jurnal Bidang Hukum Islam, 2023)
This research aims to know and understand the existence of hijab as an effort to protect muslim women from the Maqāṣid al-Syarī'ah Perspective. The method used in this study is library research with a qualitative descriptive type of research, using normative and philosophical approaches. The results of the study found that the hijab has an important role in Islam. Some of the urgency of the hijab, namely the hijab as a form of obedience to Allah swt. and His Messenger, the hijab can reduce various kinds of slander, and more importantly the hijab makes women more respectable and protected. Hijab protects women by covering their nakedness and curves and the beauty they have so that they do not cause slander and do not invite lust or dirty thoughts for those who look at them. The hijab order was revealed by Allah swt. certainly has benefit both in this world and in the hereafter. By wearing the hijab, the religion, soul, intellect, property and lineage of a Muslim woman will be maintained.